Adaptive strategic analysis models in a volatile market: case studies of today’s organizations - A. E. Bogomaz; A. G. Dmitriev (Путеводитель предпринимателя)
Adaptive models of strategic analysis are crucial in unstable market conditions for modern organizations. These models assist organizations in identifying and responding to the changing business environment, ensuring their sustainable development and competitive market position. The use of adaptive management allows companies to make flexible and informed decisions considering the impact of digitalization on business relationships. Factors such as leadership, culture, structure, and business strategy play an essential role in supporting organizational changes and adaptation. This paper discusses the fundamentals of adaptive management, including models of strategic analysis and strategic management. It covers the theoretical foundations of adaptive management, organizational structures with an adaptive management type, adaptive analysis models, and provides examples of companies that employ various tools. Additionally, a model of adaptive organizational management is developed, enabling companies to evolve in uncertain conditions. This model includes three subsystems: diagnostic of premises, selection of the optimal option, and implementation of the strategic scenario. The article concludes that adaptive strategic management is quite relevant in the context of variability and high environmental uncertainty; however, the strategy should not remain static.